Hadits-Hadits Tentang Kafa’ah dan Mahar Pendekatan Sosiologis dan Teologis Normatif - Fathullah; Syamsurii; Sayehu (Ikatan Dai Indonesia, 2024)
The issue of kafa'ah in marriage is very important in order to foster harmony in married life. Why is it so important to pay attention? because it is often found that families who have been running a household, after many years, problems suddenly arise, which are only discovered later as a result of a lack of compatibility in terms of economics, morals, social strata, education and hobbies. Marriages are carried out only with the capital of likes and likes, mutual love and true belief that with this capital they will be happy. Hadiths about kafa'ah and dowry provide guidance on the importance of equality and responsibility in marriage. Sociologically, the concepts of kafa'ah and dowry help maintain stability and harmony in the household and society. From a normative theological perspective, both of them emphasize the importance of maintaining religious values ​​and justice in marriage. Even though there have been changes in the interpretation and application of these concepts in modern society, the essence of Islamic teachings regarding kafa'ah and dowry remain relevant as guidelines for living a blessed domestic life.